Diketopyrrolopyrrole Based Organic Semiconductor Materials for Field-Effect Transistors - Zou, Xiangyu; Cui, Shuaiwei; Li, Junqiang; Wei, Xueling; Zheng, Meng (Frontiers in Chemistry, 2021)
Over the past several decades, organic conjugated materials as semiconductors in organic field effect transistors (OFETs) have attracted more and more attention from the scientific community due to their intriguing properties of mechanical flexibility and solution processability. However, the device fabrication technique, design, and synthesis of novel organic semiconductor materials with high charge carrier mobility is crucial for the development of high-performance OFETs. In the past few years, more and more novel materials were designed and tested in the OFETs. Among which, diketopyrrolopyrrole (DPP) and its derivatives, as the electron acceptors to build donor-acceptor (D-A) typed materials, are the perspective. In this article, recently reported molecules regarding the DPP and its derivatives for OFETs application are reviewed. In addition, the relationship between the chemical structures and the performance of the device are discussed. Furthermore, an outlook of DPP-based materials in OFETs with a future design concept and the development trend are provided.